Alien to this World: Politico-ontological notes on the question of alienation in apocalyptic narratives. - D'Angelo, Valerio (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
The article aims to explore the concept of the world as it has been formulated in some Western apocalyptic narratives. I will tackle the notion of world from what Taubes has defined as a keyword of apocalypticism: alienness or exile. Although barely explored, the notion of alienness runs through the main Western philosophic-political traditions, from ancient Gnosticism to modern revolutionary movements, and still echoes today as the feeling of estrangement in an ecologically devastated earth. However, far from being a unified and all−encompassing concept, alienness is two-sided. On the one hand, it expresses the Gnostics' hatred of the world as well as modern apocalyptic nihilism based on a dualistic ontology that completely separates man from the world; on the other hand, it represents a certain Stimmung that is also typical of the apocalypse but, unlike the first, signals the need for an ontological restructuring between man and the world. Against the first narrative, which has been majoritarian in Western metaphysics, I will explore the posthumous work of the Italian anthropologist Ernesto de Martino The End of the World as a way to rearticulate the relationship between the man and the world on a non-dualistic metaphysical basis. Lastly, I will frame the feeling of alienness inside our current ecological catastrophe, showing that while a Gnostic understanding grounds the hatred toward the world and nature, the second one provides, on the contrary, a broader view of being-in-the-world that asks for a community reunion with the surrounding nature and the fellow nonhuman beings.